IMPACT OF CHRONIC EXPOSURE TO HEAVY METAL MIXTURES ON SELECTED BIOLOGICAL PARAMETERS OF FRESHWATER FISH SPECIES - Saima Naz; Ahmad Manan Mustafa Chatha; Qudrat Ullah; Babar Maqbool; Alam Zeb Khan; Muhammad Zubair; Shujaat Hussain; Atta Ur Rehman (Journal of Animal and Plant Sciences, 2023)
Heavy metal contamination usually causes depletion in feed utilization in fish, and such disturbance may result in reduced metabolic rate and hence causing reduction in their growth. The present study assessed the harmful effect of sub-lethal concentrations of four different heavy metal mixtures i.e., Mix-I (Mn+Ni), Mix-II (Mn+Ni+Pb), Mix-III (Mn+Pb+Zn+Fe), and Mix-IV (Mn+Ni+Pb+Zn+Fe) on five fish species including Labeo rohita, Catla catla,Cirrhina mrigala, Hypophthalmichthys molitrix, and Ctenopharyngodon idella. The experiment was carried out in triplicate for each species separately in glass aquarium for 12 weeks. The results showed a significant (p < 0.001) effect on the treated group as compared to the control group. The average weight gain was as C. catla > L. rohita > C. mrigala > C. idella > H. molitrix. The condition factor was as C. idella > C. mrigala > L. rohita > C. catla > H. molitrix. Similarly, the feed intake also reduced significantly (p>0.001) in the treated group, and the feed conversion efficiency showed significant (p>0.05) effect of metal mixtures on fish metabolism and growth activity. The current study concluded that the studied heavy metals are toxic to different fish species, even at sub-lethal concentrations, and affect different biological parameters of fish growth.
Keywords: heavy metals; chronic exposure; freshwater fishes; growth performance; feed conversion efficiency